Modelling the Spread of HIV/AIDS Epidemic (Communications in Mathematical Research, 2021)
In this paper, a deterministic mathematical model for the spread ofHIV/AIDS in a variable size population through horizontal transmission is considered.The existence of a threshold parameter, the basic reproduction number, is established,and the stability of both the disease-free equilibrium and the endemic equilibrium isdiscussed in terms of $R_0$.
Keywords: spread of HIV/AIDS; horizontal transmission; threshold; stability.